Pesantren dan Kemandirian Ekonomi: Studi Kasus Di Pondok Pesantren Belitang OKU Timur Indonesia - Ali Muhtarom; Subandi Subandi; Muhamad Agus Mushodiq (KURAS Institute, 2024)
In Indonesia, Islamic boarding schools have the potential to achieve economic independence. This study aims to examine the efforts of three pesantrens in Belitang, East Oku, Indonesia to attain economic self-sufficiency without relying on government assistance. The research utilized a descriptive qualitative method with a case study approach. Data was collected through observation, direct interviews with relevant individuals, and documentation. The data was then analyzed through data reduction, presentation, and drawing conclusions. The focus of the study was Darul Huda Islamic Boarding School, Subulussalam, and Darul Falah Belitang. The research found that the three Belitang East OKU Islamic Boarding Schools achieved economic independence by establishing business units. The boarding schools played a crucial role in enhancing economic independence through the involvement of caregivers, nurturing students, administrative staff, managers of the Boarding School-Owned Enterprises, and administrative personnel in line with the boarding school policies. However, this approach also comes with weaknesses and risks, which can be addressed by maximizing the potential opportunities present in each business unit.